PCNA-Ub polyubiquitination inhibits cell proliferation and induces cell-cycle checkpoints. Issue 24 (16th December 2016) - Qin, Zhoushuai; Bai, Zhiqiang; Sun, Ying; Niu, Xiaohong; Xiao, Wei
ABSTRACT: In response to replication-blocking lesions, proliferating cell nuclear antigen (PCNA) can be sequentially ubiquitinated at the K164 residue leading to 2 modes of DNA-damage tolerance, namely translesion DNA synthesis (TLS) and error-free lesion bypass. Ectopic expression of PCNA fused with ubiquitin (Ub) lacking the 2 C-terminal Gly residues resembles PCNA monoubiquitination-mediated TLS. However, if the fused Ub contains C-terminal Gly residues, it is further polyubiquitinated and inhibits cell proliferation. Unexpectedly, the polyubiquitination chain does not require any surface Lys residues and is likely to be head-to-tail linked. Such PCNA polyubiquitination interferes with replication, arrests cells at the S-phase and activates the p53 checkpoint pathway. The above cell-cycle arrest is reversible in an ATR-dependent manner, as simultaneous inhibition of ATR, but not ATM, induces apoptosis. Since ectopic expression of PCNA-Ub also induces double-strand breaks that colocalize with single-stranded DNA, we infer that this non-canonical PCNA poly-Ub chain serves as a signal to activate ATR checkpoint and recruit double-strand-break repair apparatus.